The Monitoring and Control Processes of a Renewable Energy Management System. (2015) - Karoly, Ronay; Dumitru, Cristian Dragoş
Abstract: This paper presents the monitoring and control processes as an important part of a renewable energy management system. The main purpose of the work is to build a management system for a commercial consumer (hydroponic greenhouse) that uses solar and biomass energy and to present the monitoring and control processes of this system. The proposed method is to use a micro-controller for the measuring of electrical and non-electrical parameters of the system, to process the data and to adapt a control process to the technological flux. The monitoring and control processes are implemented locally with USB-Serial connections to a PC, or from a web application. This approach leads to an easy management of new or existing systems by following and optimizing the technical processes and by obtaining energy efficiency.